(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Female sensuality encircles wide range of behaviours and activities, including female sexual identity and etiquette. Many dimensions of female sexuality have been addressed by various societies and religions of the world, pertaining to biological sex, orientations and attitudes. A sufficient sexual appetite and libido in adults are essential for continuation of race. It also nurtures psychological health and immune functions. In case of hypoactive sexual desire, there will be recurrent deficiency or absence of interest and receptivity to sexual activities which causes distress and many interpersonal difficulties in fledged adult life. Flibanserin is the latest approved drug for the treatment of hypoactive sexual desire disorder in female. It generally functions on the activity and the role of neurotransmitters affecting mood and drives. Flibanserin has affinity with serotonin autoreceptor (5-HT1A) and dopamine receptor (D4). It is a full-fledged agonist of 5-HT1A in prefrontal cortex region and partial agonist in the CA3 region of hippocampus. It also acts as partial agonist of dopamine receptor (D4) but it has poor antagonist property with 5-HT2A, 5-HT2B and 5-HT2C receptors. Flibanserin declines neuronal firing rate generally in the cells of hippocampus, dorsal raphe and cortex region of brain. Hence, it can assist to improve the brain activation pattern and drives of hypoactive women.